The museum as an ecosystem: synthesis of architecture, design and landscape in museum design - Fomina, Elina Vladislavovna; Barsukova, Nataliya Ivanovna (Урбанистика, 2024)
The object of this research is modern museum complexes located in an urban or natural environment and aimed at connecting with the surrounding space. The subject of the research is the principles and design techniques of organizing the subject-spatial environment of modern museums, existing in close unity of architecture, design and landscape. Design techniques for the formation of an integral museum environment using landscape and design methods of shaping are revealed. The study focuses on the design potential of combining the interior, exterior and adjacent territories in order to preserve regional characteristics, natural and cultural environment. The article provides a comprehensive overview and classification of design concepts of museums, reveals the principles of combining cultural and educational functions of museums with sports and recreational ones. A systematic analysis of modern museum environment projects is carried out in the unity of axiological, ecological, artistic, aesthetic and contextual approaches. Based on this, the principles of organizing the museum environment as an ecosystem are identified and classified. The authors introduce the concept of "museum ecosystem". The main features of museum ecosystems are formulated. The design methodology of an ecologically appropriate human habitat synthesizing technical, social and artistic solutions is proposed, the main methods of designing artificial ecosystems are identified using the example of modern museums. The conclusion is made about the trend of designing museum complexes as integral ecosystems, it is noted that the design of modern museum complexes, when achieving the synthesis of natural forms, design tools and high technologies, allows you to organize the museum environment as an ecosystem with high comfort indicators without disturbing the natural environment.